Factors that influence patients' satisfaction with peri-partum care in Germiston Hospital maternity unit. - Khumalo, Nonhlanhla (My University, 2014)
Introduction Patient satisfaction is an important outcome of health care services and is regarded as one of the desired outcomes of care. Not much research has been done to measure satisfaction with maternity care services, especially in South Africa. Against this background this study aims to explore factors that influence women’s satisfaction with peri-partum care at Germiston hospital maternal unit. Methods: This cross-sectional descriptive study was done among 260 women aged 18 years and above during the first three days of the postpartum period. A structured questionnaire was used to gather information. The factors studied were: pain relief, cleanliness, privacy, health education, and information and participation in decision making about their care. Data capture and analysis was done using STATA 10 statistical software. Frequency tables were used to describe data and Chi-square test was used to test for association between patient satisfaction and marital status, level of education and pain relief. Results: Sixty eight percent and 63% of patients respectively were not satisfied with pain relief during labour and after delivery. A majority of women ninety seven percent were satisfied by how privacy was maintained by both nonmedical and medical staff. Ninety percent of the respondents were satisfied with the cleanliness of the environment. Less than fifty percent of women were satisfied with the information that was given to them by the doctors in order to make informed choices about their care in contrast to 63 % of women who were satisfied with the information that they got from the nurses. A majority of women 73% were not satisfied with the number of times that the health care providers asked for their opinion in planning their care. There was no association between the level of satisfaction and marital status, level of education and pain relief. Conclusion: There were varying levels of satisfaction with services during labour. Cleanliness, privacy and information sharing by nurses were viewed by women as adequate. In contrast pain relief, time spent explaining procedures and information sharing by doctors was rated as unsatisfactory. These three factors should be taken into account when designing quality improvement programmes in the maternity department.
Keywords: Patient Satisfaction